Dialectal speech self–evaluation and vitality: Šakiai and Jurbarkas sub-dialects in the beginning of the twenty-first century - Bakšienė, Rima (Lietuvių kalba, 2015)
Šakiai and Jurbarkas sub-dialects belong to the northern part Western Highlanders of Kaunas region. There is described location of this area in the Lithuanian dialect classification, specific features, dialectal speech self–evaluation and vitality in the beginning of the twenty-first century. According research results Šakiai and Jurbarkas sub-dialects constitute an integral area. there are many common features, this area is transitional to Lowlanders dialect. Dialectal speech self–evaluation is different between two dialects. The Šakiai dialect speakers fully aware of its dialectal dependence, they are able to define its own dialect. However, dialect users note little dialectal features in their own speech, dialectal identity more based on geographical Location and administrative division. The Jurbarkas dialect speakers more fail to identify themselves can not to define its own dialect. The dialect names mostly are made by places of residence names. However, users of this dialect more note dialectal features. Dialectal speech prestige and vitality is high in both sub-dialects. The code switching is uncharacteristic to this area. The least noticeable features are stable, the most noticeable features most disappearing. There are not observed distinct features of the new dialect. High vitality of the dialectal speech is based on small difference from the standard language, not on dialectal prestige or linguistic provisions of dialect speakers.
Keywords: sub-dialect; Highlanders; dialect classification; Šakiai; Jurbarkas; dialectal features; dialectal identity